Measuring the impact of inventory control practices: A conceptual framework - Radzuan, Kamaruddin; Othman, Abdul Aziz; Anuar, Herman Shah; Osman, Wan Nadzri (2014)
Inventory control provides method to manage the flow of materials or goods in the supply chain. Since controlling inventory is not the only mechanism to ensure an adequate inventory levels, it is also able to reduce inventory related cost. The manufacturing sector holds large inventories with quite complicated process and policy related to inventory control, especially when involving external party whether they are supplier or customer The manufacturing companies always confront with issues related to inventory management, which includes bullwhip effect on demand, increase of inventory cost, late delivery, and inventory shortage. Therefore, a key challenge for manufacturing company is to determine how to control the inventory flows effectively as to get the best overall inventory performance. Since inventory control manages to cover a wide range of aspects, it is chosen to focus on specific element such as inventory monitoring and ordering; control limits; and replenishment decisions.Lacking of an inventory control practices that normally occurred among manufacturing companies had lead this paper to propose a framework on inventory control practices to acquire that knowledge.